Radiographic pelvimetry and evaluation of radiographic findings of the pelvis in cats with dystocia - Celimli, N.; Seyrek Intas, D.; Yilmazbas, G.; Seyrek Intas, K.; Keskin, A.; H. Kumru, I.; Kramer, M. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2008)
Objective: The aim of this study was to determine reference values for pelvic dimensions in radiographically unremarkable native Turkish cats (similar to European Shorthair cats) and to evaluate radiographic findings of the pelvis in cats with dystocia and to compare their pelvimetric measurements with those of radiographically unremarkable cats. Material and methods: Pelvimetry was performed on ventro-dorsal and lateral radiographs of radiographically unremarkable male (n = 34) and female cats (n = 23) with no history of dystocia and cats presented with dystocia. Cats with dystocia were classified in groups according to radiographical findings: cats without obvious radiographical changes, cats with traumatic pelvic stenosis and cats with pelvic narrowing due to metabolic disease. Statistical analyses were performed to find out significant differences between both groups with respect to gender and age. Results: Pelvic dimensions of radiographically unremarkable cats are greater in males compared to females. These differences increase with increasing age, but are not significant in cats older than 2 years. Twenty-five out of 37 queens presented with dystocia had significantly smaller pelvic dimensions compared to radiographically unremarkable queens. Deformation/narrowing of the pelvis in 12 cats (32%) due to old fractures and metabolic bone disease occurred in 7 and 5 cases, respectively. Conclusion: Old, untreated pelvic fractures and metabolic disorders may cause stenosis of the birth canal and dystocia. However, there is a high rate of queens without deformation, but smaller pelvic dimension experiencing dystocia. As 80% of these cats are around 1 year of age they might still be growing or are underdeveloped, despite pelvic physeal growth plates are already closed. Clinical relevance: Pelvic radiographs and pelvimetry before mating enables to identify cats with pelvic narrowing due to traumatic, metabolic, or developmental reasons and may prevent the queen from potential dystocia.
Keywords: Feline; pelvic dimensions; measurements; metabolic disorders; pelvic fracture